The Importance of Innovation in Learning Poetry Using Various Media at Elementary School Level: A Literature Review - Indra Rasyid Julianto; Diardana Prima Sintasari; Widya Gusvita; Rifa'atussalwa Hayati; Pramisdi Winanto Saputro (Educational Insights, 2025)
This study serves as a reference to understand that teachers have access to a variety of instructional media that can be optimally utilized in teaching poetry writing at the elementary level. It highlights how digitalization in education requires teachers to continuously innovate in their teaching practices. The appropriate use of media makes the process of learning poetry writing more accessible and easier to grasp. These media tools assist students in interpreting the meaning conveyed through various forms of content. With the support of media, students are able to compose poems in a more systematic and structured manner. The teacher's role in delivering the material also plays a crucial part in ensuring the smooth flow of the learning process. Integrating media into poetry instruction creates a fresh and engaging learning environment for students, moving beyond textbooks or methods that may be difficult to comprehend. This research adopts a qualitative descriptive method, using literature review from a range of relevant articles to support the investigation.